2017
DOI: 10.7567/jjap.56.091003
|View full text |Cite
|
Sign up to set email alerts
|

Improved hysteresis in a normally-off AlGaN/GaN MOS heterojunction field-effect transistor with a recessed gate structure formed by selective regrowth

Abstract: A normally-off AlGaN/GaN MOS heterojunction field-effect transistor (MOS-HFET) with a recessed gate structure formed by selective area regrowth is demonstrated. The fabricated MOS-HFET exhibits a threshold voltage of 1.7 V with an improved hysteresis of 0.5 V as compared with a device fabricated by a conventional dry etching process. An analysis of capacitance–voltage (C–V) characteristics reveals that the dry etching process increases interface state density and introduces an additional discrete trap. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A particularly large I DS hysteresis and V T ∼ 0 V was observed after the etching, which was the HEMT initial vital stage, after only marginal current of the virgin (un-etched) device. Large hysteresis is often a consequence of deep levels and trapping in the MOS gate stack, particularly in normally-off HEMTs, 25,26) and increases with applied V GS . [27][28][29] After the passivation hysteresis was largely eliminated, most likely because of decreased V T and low V GS of the normally-on operation.…”
Section: Resultsmentioning
confidence: 99%
“…A particularly large I DS hysteresis and V T ∼ 0 V was observed after the etching, which was the HEMT initial vital stage, after only marginal current of the virgin (un-etched) device. Large hysteresis is often a consequence of deep levels and trapping in the MOS gate stack, particularly in normally-off HEMTs, 25,26) and increases with applied V GS . [27][28][29] After the passivation hysteresis was largely eliminated, most likely because of decreased V T and low V GS of the normally-on operation.…”
Section: Resultsmentioning
confidence: 99%
“…The V/III ratio was kept constant and was 2790. In order to evaluate the crystallinity of the grown film, X-ray rocking curves of (0002) plane and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) plane were measured. Cathode luminescence (CL) method at RT was used for evaluation of dislocation density of the grown film.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…2, an improvement of the FWHM values of the (0002) plane was observed with increasing growth rate. On the other hand, the FWHM values of the asymmetric (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) plane was deteriorated at 3 μm h −1 or more. The behavior of X-ray rocking curves for these growth rates is not the specificity in GaN growth on SCAMO, and a similar trend was also observed in GaN growth on sapphire.…”
Section: Growth Of Gan On Scamo Substratesmentioning
confidence: 97%
See 1 more Smart Citation
“…[9,10,13] Another approach to achieve normally off devices is a selective area regrowth (SAG) technique to enable the formation of the recessed-gate structure without dry etching. [14][15][16][17] Our group recently reported the fabrication of recessed-gate MOSFET without degradation of a gate stack by SAG. [18] It was also found that surface treatment of a GaN template before regrowth is important for improving the electrical properties of AlGaN/GaN heterostructure.…”
mentioning
confidence: 99%